Modelagem termodinâmica do equilíbrio de fases em sistemas aquosos visando a recuperação dos íons cloreto e potássio de salmouras naturais - Ruberlan Gomes da Silva (2014)
Chemical fertilizers, such as, potassium chloride (KCl), potassium sulphate (K2SO4), monoammonium phosphate (MAP or NH4H2PO4), diammonium phosphate (DAP or (NH4)2HPO4) and ammonium nitrate (NH4NO3), and other chemical products (for instance sodium hydroxide (NaOH) and soda ash (Na2CO3)), are produced from electrolyte solutions or brines with a high content of soluble salts. Some of the products mentioned above are manufactured by fractional crystallization, process where several salts are separated as solid phases with a high degree of purity (>90%) by evaporation of water present in the composition of multicomponent electrolyte solutions or brines. Due to the high world demand for the products, it is necessary to have a good knowledge about the thermodynamic models used to estimate the compositions of salts and brines obtained by fractional crystallization of multicomponent electrolyte solutions or brines. The Pitzer e Harvie´s model was used to calculate the composition of crystallized salts after remove water from multicomponent electrolyte solutions or brines representing the quinary system NaCl-KCl-MgCl2-CaCl2-H2O at 293K. The temperature of 293K represents the medium brine temperature in saline deposits located in South America, especially in Salar de Atacama in Chile. Initially, the mineral solubilities of binary systems (NaCl-H2O, KCl-H2O and MgCl2- H2O) and ternary system (KCl-MgCl2-H2O) were calculated at 293K and compared with literature data. The results show that Pitzer and Harvie´s model represents well the binary and ternary systems. The phase diagrams of solutions with high ionic strength were also plotted against the experimental data from tests with synthetic pulps and a natural brine representative of quinary system NaCl-KCl-MgCl2-CaCl2-H2O at 293K. The tests with synthetic and natural brines, containing the salts NaCl, KCl, MgCl2 and CaCl2, were performed and compared to the model. The results show that the Pitzer e Harvie´s model can be used to estimate the chemical composition of the salts produced during fractional crystallization of solutions containing NaCl, KCl, MgCl2 and CaCl2. The model can be used to do a material balance in the solar pond with the objective to recover potassium chloride by fractional crystallization of a natural brine containing several salts dissolved, for instance, NaCl, KCl, MgCl2 and CaCl2.